IL-1 Family Members Mediate Cell Death, Inflammation and Angiogenesis in Retinal Degenerative Diseases - Wooff, Yvette; Man, Si Ming; Aggio-Bruce, Riemke; Natoli, Riccardo; Fernando, Nilisha (Frontiers in Immunology, 2019)
Inflammation underpins and contributes to the pathogenesis of many retinal degenerative diseases. The recruitment and activation of both resident microglia and recruited macrophages, as well as the production of cytokines, are key contributing factors for progressive cell death in these diseases. In particular, the interleukin 1 (IL-1) family consisting of both pro- and anti-inflammatory cytokines has been shown to be pivotal in the mediation of innate immunity and contribute directly to a number of retinal degenerations, including Age-Related Macular Degeneration (AMD), diabetic retinopathy, retinitis pigmentosa, glaucoma and retinopathy of prematurity (ROP). In this review, we will discuss the role of IL-1 family members and inflammasome signalling in retinal degenerative diseases, piecing together their contribution to retinal disease pathology, and identifying areas of research expansion required to further elucidate their function in the retina.